Mechanical and viscoelastic behavior characterization of hybrid aluminum/carbon fiber/pineapple leaf fiber composite via VARTM for automotive industry - Xiao, Hanyue; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant (Taylor and Francis, 2024)
Hybridizing natural and synthetic fibers is thought to be an alternate technique for achieving the desired balance between the mechanical performance and sustainability of fiber metal laminates (FMLs). The aluminum (Al)/pineapple leaf fiber (PALF)/carbon fiber (CF) reinforced epoxy composites with five stacking sequences were fabricated by the vacuum-assisted resin transfer molding (VARTM) method. The effects of the hybridization and layering sequence on mechanical and viscoelastic properties have been investigated by the hardness, interlaminar shear strength (ILSS), and Izod impact test, along with dynamic mechanical analysis (DMA). The study found that A1 (ACPCA) showed significant improvements over non-hybrid AP (APPPA), with 86.50% better ILSS and 59.59% higher impact strength. Compared to A2 (APCPA), A1’s ILSS and impact strength were 26.26% and 38.38% better, respectively, due to two CF layers. Hybrid FML A3 (CPAPC) had the lowest impact strength at 97.77 kJ/m2 among FMLs with aluminum outer layers. DMA tests showed all hybrids were stiffer than non-hybrid AP, with A1 having superior viscoelastic properties. This suggests PALF and CF in natural fiber metal laminates (NFMLs) could be promising for automotive applications.